Study of Water Quality Suitability in Sub-Watersheds for Tilapia, Gurame, and Catfish Farming in Lingsar Subdistrict, West Lombok Regency - Awan Dermawan; Bagus Dwi Hari Setyono; Andre Rahmat Scabra; Muhammad Marzuki; Syawalina Fitria; Salwa Suhendri (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the suitability of water quality in the Lingsar Sub-watershed, West Lombok, for the cultivation of tilapia (Oreochromis niloticus), gourami (Osphronemus gouramy), and catfish (Clarias gariepinus). Field measurements were conducted during June–July 2024 across several sampling points. Key water quality parameters were assessed and compared with established aquaculture standards and the physiological requirements of each species. The findings indicate that the general water quality conditions, including temperature, pH, dissolved oxygen, and levels of nitrogen compounds, support the growth of all three species. The sub-watershed is highly suitable for more tolerant species such as catfish and tilapia, while gourami cultivation is also feasible with more intensive management. It is concluded that the Lingsar Sub-watershed holds considerable potential for development as an integrated aquaculture zone. Sustainable development through regular water quality monitoring and the adoption of eco-friendly technologies is recommended.